Seascape context modifies how fish respond to restored oyster reef structures. (18th February 2019) - Gilby, Ben L; Olds, Andrew D; Henderson, Christopher J; Ortodossi, Nicholas L; Connolly, Rod M; Schlacher, Thomas A
Abstract: The seascape context of coastal ecosystems plays a pivotal role in shaping patterns in fish recruitment, abundance, and diversity. It might also be a principal determinant in structuring the recruitment of fish assemblages to restored habitats, but the trajectories of these relationships require further testing. In this study, we surveyed fish assemblages from 14 restored oyster reefs and 14 control sites in the Noosa River, Queensland, Australia, that differed in the presence or absence of seagrass within 500 m, over four periods using baited cameras. Fish assemblages at oyster reefs differed from those at control sites, with higher species richness (1.4 times) and more individuals of taxa that are harvested by fishers (1.8 times). The presence or absence of seagrass nearby affected the abundance of a key harvestable fish species (yellowfin bream Acanthopagrus australis ) on oyster reefs, but not the overall composition of fish assemblages, species richness, or the total abundance of harvestable fishes overall. These findings highlight the importance of considering species-specific patterns in seascape utilization when selecting restoration sites and setting restoration goals, and suggest that the effects of restoration on fish assemblages might be optimized by focusing efforts in prime positions in coastal seascapes.